Tissue response to five commercially available peritoneal adhesion barriers: a systematic histological evaluation - Schmitt, Volker H.; Mamilos, Andreas; Schmitt, Christine; Neitzer-Planck, Constanze; Rajab, Taufiek Konrad; Hollemann, David; Wagner, Willi Linus; Krämer, Bernhard; Hierlemann, Helmut; Kirkpatrick, C. James; Brochhausen, Christoph (Journal of biomedical materials research. Part B, Applied biomaterials, 2017)
Separating wounded serosa by physical barriers is the only clinically approved adjunct for postoperative adhesion prevention. Since the optimal adhesion barrier has not been found, it is essential to improve our pathogenic understanding of adhesion formation and to compare the effects of different barrier materials on tissue and cells. Wistar rats underwent standardized peritoneal damage and were treated either with Seprafilm, Adept, Intercoat, Spraygel, SupraSeal or remained untreated as a control. 14 days postoperatively, the lesions were explanted and histomorphologically analyzed using the European ISO score to evaluate material implants. Striking differences between the material groups were present regarding the inflammation, fibrosis, and foreign body reaction. According to the ISO score, Intercoat and Spraygel were considered as nonirritating to tissue. Adept, Seprafilm, and SupraSeal were assessed as mild‐irritating materials. Interestingly, the most effective material in adhesion prevention revealed moderate inflammation accompanied by minor fibrosis. The degree of inflammation to barrier materials does not predict the efficacy in the prevention of adhesions. Histopathological investigations are crucial to improve our understanding of the cellular mechanisms during adhesion formation and elucidate the tissue response to material approaches used in adhesion prevention. This will lead to improved antiadhesive strategies and the development of functional barrier biomaterials.